Comparing the Effect of Green Tea and Peppermint Mouthwashes on Halitosis: A Cross-over randomized Single-blind Clinical Trial - Bakhshi , Mahin; Kamalinejad , Mohammad; Goodarzi, Saideh; Namdari, Mahshid; Tofangchiha , Maryam; Dalirani, Sara; Ladan Moghaddam, Mahsa (Journal of Dental School, 2024)
Introduction: Herbal remedies can have a preventive role in malodor. This study aimed to investigate the clinical effect of green tea and peppermint on halitosis. Materials and Methods: This study was a randomized clinical trial. Eighty-eight volunteers with an average organoleptic score of ≥2 were enrolled. The volunteers underwent two one-week phases of treatment with green tea or peppermint mouthwashes separated by a washout period of one week. Main outcomes included the objective and subjective assessment of eventual changes in malodor. Organoleptic assessment was used as objective measure and self-perception of mouthwashes taste and smell as subjective one. Results: The decrease in halitosis severity was significant in green tea or peppermint mouthwashes (P<0.001). There was no significant difference between the decrease in organoleptic level (P=0.72). There was no significant difference between both mouthwashes regarding self-assessed satisfaction (P=0.78). Conclusion: Both mouthwashes were useful in managing halitosis. Hence, considering the taste of individuals, each of them can be prescribed to halitosis treatment.